Serum Markers Measured in FNA Fluids of Medullary Thyroid Carcinoma Occurring as a Cyst. Issue 2 (April 2016) - Trimboli, Pierpaolo; Guidobaldi, Leo; Locuratolo, Nicola; Piro, Francesca R.; Giordano, Marco; Giovanella, Luca
Background: Diagnosis of medullary thyroid carcinoma (MTC) is still a challenge, and the measurement of calcitonin in fine-needle aspiration (FNA) washout has been recently introduced. Rarely, MTC presents as a cyst and its preoperative detection is difficult. Methods: A 66-year-old woman was referred to us with high serum calcitonin. Ultrasound evaluation showed one cystic and one solid nodule. FNA was performed in both nodules and calcitonin, procalcitonin and CEA were measured in the aspirate fluids. Results: The markers showed elevated levels in the FNA washout of the cyst and the patient was operated on. Final histology demonstrated MTC of the cystic nodule. Four weeks later, all serum markers were undetectable. Conclusions: In the presence of a cystic thyroid lesion the diagnosis of MTC should be taken into account, and measuring calcitonin in FNA fluid is relevant. The determination in FNA of other markers is technically feasible but its role should be evaluated in larger series.